Implementasi Metode Pembelajaran Fishbowl Diskusi dalam Meningkatkan Prestasi Belajar Siswa pada Mata Pelajaran Fiqih di Kelas XI B Madrasah Aliyah Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun Ajaran 2024/2025: Penelitian - Azhari, Nazar; Hasan, Mustaqim; Nugraha, Hendika Adi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The implementation of the Fishbowl discussion learning method in the Fiqh subject has proven effective in creating a more active, participatory, and reflective learning environment. By dividing students into two groups—the inner circle for discussion and the outer circle as observers—this method encourages students to express ideas more confidently, listen attentively, and develop analytical thinking and communication skills. The learning process is no longer teacher-centered, but rather driven by dynamic student-to-student interactions, which directly enhances understanding of Fiqh concepts and positively impacts learning outcomes. This study uses a qualitative approach with a descriptive method. Data collection was conducted through classroom observation, in-depth interviews with teachers and students, and documentation of learning activities. The data were analyzed thematically to identify implementation patterns, supporting factors, and challenges faced in applying the Fishbowl method in class XI B at Madrasah Aliyah Hidayatul Mubtadiin. The results of this method’s implementation show a significant increase in student engagement, both intellectually and emotionally. Students became more enthusiastic about participating in lessons, gradually got accustomed to discussion-based learning, and began to internalize Fiqh values in their daily lives. Academic performance also improved alongside the growth in students’ confidence to present and defend their arguments. Nevertheless, the implementation of this method still encountered challenges such as time constraints during learning sessions, unequal speaking abilities among students, and the lack of facilities that support optimal discussion-based learning in the classroom. Several challenges that arise during the application of the Fishbowl method can actually be mitigated through appropriate strategies. Effective time management, forming small discussion groups, and employing inclusive and supportive teacher approaches are all helpful in overcoming these obstacles. As a result, this method can still be applied effectively despite existing limitations. This suggests that the success of the Fishbowl method heavily relies on the teacher's preparedness and the flexibility of implementation strategies in real classroom situations.